Da formação acadêmica à atuação em educação física adaptada: a preparação do profissional de educação física para o contexto inclusivo escolar - Venditti Júnior, Rubens [UNESP]; Silva, Jenefer Santos; Silva, Priscila Vieira da; Alencar, Valessa Kalyne Araújo (My University, 2013)
This study examines the knowledge of the physical education teacher’s relation with inclusion of handicapped people in their classes. Thus, data were collected through a semi-structured questionnaire administered in 23 teachers of Physical Education. The main difficulties to the implementation of inclusion concerned basically to the lack of applied knowledge. As suggestions, were highlighted: the need for guidance by a multidisciplinary team; continuing education; upgrades in infrastructure and appropriate teaching resources; previous experience of teaching students with disabilities were also related. The data allowed the identification of elements needed to accomplish the inclusive educational physical education purpose and the need of professional prepare to attend the inclusive quests.

O presente estudo analisa o conhecimento do professor de Educação Física (EF) em relação à inclusão de pessoas com deficiência em suas aulas de EF escolar. Para isto, foram coletados dados por meio de um questionário do tipo semi estruturado, aplicado a 23 professores de EF Escolar. As principais dificuldades indicadas para a realização da inclusão referiram-se basicamente à falta de conhecimento aplicado. Como sugestões se destacaram: necessidade de orientação por equipe multidisciplinar; formação continuada; melhorias na infraestrutura e recursos pedagógicos adequados. Experiências prévias junto a alunos com deficiências também foram muito destacadas. Os dados permitiram identificar vários aspectos necessários à efetivação da proposta inclusiva para a EF escolar e a necessidade de preparação do profissional de EF para atender estas demandas.
From academic formation to acting in adapted physical education: a preparation of physical education teacher for scholar inclusive contexts
Keywords: Inclusive education; Physical education; Vocational training; Disabled person; Educação inclusiva; Educação física; Formação profissional; Pessoas com deficiência